Influence of host plant and rice straw as substrate on mass multiplication of arbuscular mycorrhizal fungi for largeâscale agricultural application - Nisha Kadian; Kuldeep Yadav; Esha Jangra; Ashok Aggarwal (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Rice straw is a waste product from the harvesting of Oryza sativa L. It is recurrently burned resulting in producing overheating, soil degradation, and air and water pollution. Method A pot experiment was designed under polyhouse conditions to evaluate the effects of rice straw as a substrate with Sorghum bicolor (L.) Moench, Hordeum vulgare L. and Triticum aestivum L. as diferent host on mass multiplication of Glomus mosseae. Results AM fungi multiplication was greatly influenced by the presence, concentration (0, 25, 50 or100 g/pot) and type of substrates. Soil amendment with compost rice straw proved more suitable for AM fungal multiplication over dry substrate. Sorghum bicolor acts as a suitable host and produced the most inoculum followed by Triticum aestivum. Conclusion Assessment of the effects of substrates and hosts on the multiplication of pure culture of AM Fungi is an important prerequisite condition for large-scale agricultural application and exploration as biofertilizers.